Dispersive surface free energy of adsorbents modified by supramolecular structures of heterocyclic compounds - Vladimir Yu. Guskov; Yulia Yu. Gainullina; Alina F. Gabdulmanova; Albina N. Gareeva (Chimica Techno Acta)
In the present work, the dispersive surface free energy was calculated by Dorris-Gray method for 30 samples of adsorbents modified with chiral supramolecular structures of uracil, 6-methyluracil, 5-hydroxy-6-methyluracil, 5-fluorouracil, thymine, melamine, cyanuric and barbirutic acids, and perylene-3,4,9,10-tetracarboxylic dianhydride. It was shown that the homologous series of n-alkanes is better suited for measuring dispersive surface free energy than the homologous series of alcohols. It was established that the classical Dorris-Gray method does not allow obtaining well interpretable data for the objects studied. This is due to a noticeable effect that inductive interactions of a polar surface as an inductor with nonpolar alkane molecules have on the calculated values. We suggested to modify the Dorris-Gray method, making it possible to obtain data on the dispersive component of the free energy of adsorption. It was shown that the changes in dispersive surface free energy as a result of the modification correlate well with data on the structure and properties of supramolecular ensembles of the modifiers used. The results obtained can be used to predict the enantioselectivity of chiral adsorbents.